Analysis of clinical phenotypes and genotypes of congenital deafness caused by rare variants in GJB2 - Zhao, Xuxu; Chi, Huan; Bai, Yan; Lu, Yu; Xiong, Wenyu; Kang, Houyong; Zhang, Cheng (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to analyze a genetic family with the GJB2 gene c.551G>A (p.R184Q) variant, exploring the relationship between its genotype and clinical phenotype, and summarizing the inheritance pattern and clinical features associated with this locus.MethodsDetailed medical history collection and physical examinations were conducted for the proband and their family members. Audiological assessments and genetic sequencing analyses were performed on some members. Additionally, a review of existing literature concerning GJB2 c.551G>A (p.R184Q) was conducted.ResultsThe proband, along with their father and paternal grandmother, carried the heterozygous mutation GJB2 c.551G>A, all exhibiting moderate to profound bilateral prelingual sensorineural deafness. Notably, the proband also presented symptoms of skin dryness and nail abnormalities characteristic of syndromic hearing loss.ConclusionThe GJB2 c.551G>A mutation not only leads to severe hearing loss but may also be associated with syndromic hearing loss, expanding our understanding of the clinical spectrum associated with this variant.